2008
DOI: 10.1021/jf072227k
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Storage Conditions on Chemical Composition and Sensory Properties of Citrus Honey

Abstract: Fresh citrus honey was stored at 10, 20, and 40 degrees C for 12 months. The effect of storage on the quality of honey was evaluated using physicochemical parameters, volatile compounds, mono-, di-, and trisaccharides, and sensory analysis. Diastase activity and HMF were out of the legal limit in honey stored 12 months at 40 degrees C. Volatile compounds (especially terpenes and terpene derivatives), monosaccharides, and disaccharides presented important losses during honey storage at any temperature. Honey st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 35 publications
10
50
3
Order By: Relevance
“…The enzymatic activity presented a decreasing behavior until 180 days of storage, but adapting at all times to the established by the current regulations. These results coincide with different reports (Castro-Vázquez et al, 2008;Ramírez Cervantes et al, 2000;Takenaka & Echigo, 1974). For the conditions evaluated, time and temperature showed effects for a level of significance of 95% (Table 1).…”
Section: Diastasesupporting
confidence: 93%
See 1 more Smart Citation
“…The enzymatic activity presented a decreasing behavior until 180 days of storage, but adapting at all times to the established by the current regulations. These results coincide with different reports (Castro-Vázquez et al, 2008;Ramírez Cervantes et al, 2000;Takenaka & Echigo, 1974). For the conditions evaluated, time and temperature showed effects for a level of significance of 95% (Table 1).…”
Section: Diastasesupporting
confidence: 93%
“…The reaction is favored by acidic conditions of the sample, accelerating the formation of HMF. This behavior described by several authors (Castro-Vázquez et al, 2008;Ramírez Cervantes et al, 2000;Takenaka & Echigo, 1974) establishes the usefulness of this indicator to evaluate the aging of honey.…”
Section: Hydroxymethylfurfuralmentioning
confidence: 55%
“…Other authors also reported depletion in diastase activity after storage for three and half months at 26°C (Ramírez Cervantes et al 2000), 1 year at 20 (±5°C) (Yilmaz and Küfrevioglu 2001), and for 2 years at 20°C (Sancho et al 1992). However, Castro-Vazquez et al (2008) stated that diastase activity for citrus honey stored for 12 months at 40°C exceeded permissible limit.…”
Section: Hmf Content and Diastase Activitymentioning
confidence: 99%
“…Based on the commercial importance of the honey aroma, it should be necessary to pay attention to the changes that occur in the volatile fraction as a consequence of long storage periods. Until now, few researches have been focused on establishing the impact of storage on the volatile profile of honeys [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…From a sensory point of view, inappropriate conditions of storage can produce odours and tastes, different to fresh honey, which could affect the sensorial quality [11]. The generation of off-flavour compounds as a result of unsuitable preservation depends largely on the storage conditions.…”
Section: Introductionmentioning
confidence: 99%